Female labor force participation in historical census microdata - Jørgen Modalsli (European Historical Economics Society (EHES), 2025)
How reliable is historical microdata? Understanding historical labor force participation is crucial for assessing long-term trends in economic development and intergenerational mobility. Most existing historical studies are, however, limited to men, and little is known about how reliable quantitative historical sources are when studying labor market outcomes for women. This paper documents that the measurement of women's economic activity in the 1910 Norwegian population census had a high level of consistency. There is extensive discussion of measurement issues in historical census reports, micro data can reproduce historical census tables with a high degree of accuracy, and other contemporary reports such as industrial censuses and tax statistics confirm the results found in the census. In addition, a double-enumeration feature of the Norwegian census is leveraged to assess consistency between enumerators, finding no indication that precision in the occupational classification of women is any lower than for men. Some potential sources of downward bias are found in the historical census microdata set provided by IPUMS. Based on the results in this paper, historical census data appears well suited to study economic activity using modern econometric methods, for women as well as men. A slight upward revision of the 39% female labor force participation in Norway in 1910 might be in order.
Keywords: J16 J21 N33; 330; Labor force participation; historical census data; gender; occupational measurement; Norway